Mitochondria-targeted antioxidant SkQ1 inhibits leukotriene synthesis in human neutrophils - Sud’ina, Galina F.; Golenkina, Ekaterina A.; Prikhodko, Anastasia S.; Kondratenko, Natalia D.; Gaponova, Tatjana V.; Chernyak, Boris V. (Frontiers in Pharmacology, 2022)
Leukotrienes are among the most potent mediators of inflammation, and inhibition of their biosynthesis, is becoming increasingly important in the treatment of many pathologies. In this work, we demonstrated that preincubation of human neutrophils with the mitochondria targeted antioxidant SkQ1 (100 nM) strongly inhibits leukotriene synthesis induced by three different stimuli: the Ca2+ ionophore A23187, the chemotactic formyl-peptide fMLP in combination with cytocholasin B, and opsonized zymosan. The SkQ1 analogue lacking the antioxidant quinone moiety (C12TPP) was ineffective, suggesting that mitochondrial production of reactive oxygen species (ROS) is critical for activating of leukotriene synthesis in human neutrophils. The uncoupler of oxidative phosphorylation FCCP also inhibits leukotriene synthesis, indicating that a high membrane potential is a prerequisite for stimulating leukotriene synthesis in neutrophils. Our data show that activation of mitogen-activated protein kinases p38 and ERK1/2, which is important for leukotriene synthesis in neutrophils is a target for SkQ1: (i) the selective p38 inhibitor SB203580 inhibited fMLP-induced leukotriene synthesis, while the ERK1/2 activation inhibitor U0126 suppressed leukotriene synthesis induced by any of the three stimuli; (ii) SkQ1 effectively prevents p38 and ERK1/2 activation (accumulation of phosphorylated forms) induced by all three stimuli. This is the first study pointing to the involvement of mitochondrial reactive oxygen species in the activation of leukotriene synthesis in human neutrophils. The use of mitochondria-targeted antioxidants can be considered as a promising strategy for inhibiting leukotriene synthesis and treating various inflammatory pathologies.